RELEVANSI PENDIDIKAN ISLAM DEMOKRATIS DALAM SURAT ALI IMRAN 159 - Mirza Mahbub Wijaya (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2020)
Abstract Educational democracy is a very important process because it will provide equal educational opportunities to all, regardless of race (ethnicity), creed, skin color and social status. The principles of democracy can be implemented in the Islamic education system because basically Islam gives freedom to individuals (students) to develop natural values that exist within themselves in line with the times. In this study, it discusses the relevance of Democratic Islamic Education in Surah Ali Imron 159. In this surah there are implicit democratic concepts such as gentleness and deliberation or communication within organizations. In the verse, it explains the steps of deliberation. Namely, being gentle, forgiving other deliberation participants, asking for their forgiveness and putting trust in after the deliberation. In this article, we will present a view of the democratic concept in Islamic education. Keywords: Education, Democratic, Islamic Education Abstrak Demokrasi pendidikan merupakan proses yang sangat penting karena akan memberikan kesempatan pendidikan yang setara kepada semua, tanpa memandang ras (suku), keyakinan, warna kulit dan status sosial. Prinsip demokrasi dapat diterapkan dalam sistem pendidikan Islam karena pada dasarnya Islam memberikan kebebasan kepada individu (peserta didik) untuk mengembangkan nilai-nilai kodrati yang ada dalam dirinya sejalan dengan perkembangan zaman. Dalam kajian ini membahas tentang relevansi Pendidikan Islam Demokratis dalam Surah Ali Imron 159. Dalam surah ini terdapat konsep demokrasi yang tersirat seperti kelembutan dan musyawarah atau komunikasi dalam organisasi. Dalam ayat tersebut dijelaskan langkah- langkah musyawarah. Yakni, bersikap lembut, memaafkan peserta musyawarah lainnya, meminta maaf dan menaruh kepercayaan setelah musyawarah. Pada artikel kali ini, kami akan menyajikan pandangan tentang konsep demokrasi dalam pendidikan Islam. Kata Kunci: Pendidikan, Demokrasi, Pendidikan Islam